2001
DOI: 10.1002/jmri.1057
|View full text |Cite
|
Sign up to set email alerts
|

Focal liver lesions: Comparison of dual‐phase CT and multisequence multiplanar MR imaging including dynamic gadolinium enhancement

Abstract: The purpose of this study was to compare dual-phase spiral computed tomography (CT) and magnetic resonance imaging (MRI) using dynamic gadolinium enhancement for liver lesion detection and characterization. Twenty-two consecutive patients underwent dual-phase spiral CT and MRI for the evaluation of focal liver disease within a 1-month period. Spiral CT and MR images were interpreted prospectively, in a blinded fashion by separate, individual, experienced investigators, to determine lesion detection and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
113
1
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(125 citation statements)
references
References 15 publications
3
113
1
8
Order By: Relevance
“…Focal liver lesions can therefore potentially be differentiated on the basis of their selective source of blood supply reflected in the timeintensity contrast enhancement curves on dynamic postgadolinium T1W imaging. 10,11 Liver specific MR contrast media take advantage of affinity of certain compounds to concentrate in hepatocytes or Kupffer cells. Gadobenate dimeglumine (Gd-BOPTA) is an intravenously administered liver specific MRI contrast medium, which has proven selective uptake by hepatocytes and subsequent biliary excretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal liver lesions can therefore potentially be differentiated on the basis of their selective source of blood supply reflected in the timeintensity contrast enhancement curves on dynamic postgadolinium T1W imaging. 10,11 Liver specific MR contrast media take advantage of affinity of certain compounds to concentrate in hepatocytes or Kupffer cells. Gadobenate dimeglumine (Gd-BOPTA) is an intravenously administered liver specific MRI contrast medium, which has proven selective uptake by hepatocytes and subsequent biliary excretion.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,13,15 The liver specificity of the contrast medium was amplified in 5 (10%) patients in the delayed imaging subset, in whom the findings of retained lesional contrast contributed to the definitive diagnosis of HCC, regenerating nodule and chronic abscess (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of benign, malignant, and inflammatory diseases of the spleen, adrenals, kidneys, pancreas, and organs of the male and female pelvis are well depicted by MRI, and in the hands of experienced practitioners are better elucidated than they would be on CT (72)(73)(74)(75)(76). The superiority of MRI over CT for detecting and characterizing focal liver lesions and liver disease is well established (77)(78)(79)(80). In patients with malignancy, MRI demonstrates an advantage over CT in detecting extrahepatic abdominal disease in many sites (81).…”
Section: Consider Alternatives To Ctmentioning
confidence: 99%
“…A logical first step to a transition in imaging ordering patterns would be to utilize MRI as the primary imaging tool to investigate diseases of the liver. The rationale for this is fourfold: 1) the intrinsic safety of the modality, contrast agents, and intravenous injection process; 2) the established greater accuracy of MRI over CT for liver investigations (78) (Fig. 1); 3) the ease of performing MRI; and 4) the ease of interpreting MRI studies, even without extensive MR training.…”
Section: Consider Alternatives To Ctmentioning
confidence: 99%
“…HRE: high relative enhancement, MRE: medium relative enhancement, LRE: low relative enhancement. Studies have already shown that MRI examination is superior to other examinations as a result of the soft tissue contrast enhancement [16,17]. The method of choice in the diagnosis and classification of liver lesions is currently dynamic contrast-enhanced MRI [18 -20].…”
mentioning
confidence: 99%